Integrasi Pendidikan Karakter Bermuatan Lokal Madura sebagai Penguatan Kesadaran Ekologi pada Kurikulum Merdeka - Wachidah, Liana Rochmatul; Albaburrahim, Albaburrahim; Fitri, Novi Amilia (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the implementation, success factors, and impacts of character education that influences Madurese local as an understanding of ecology in the Independent Curriculum. The research method used is qualitative with a collective case study approach. The locations are SMPN 1 Larangan, SMPN 4 Pamekasan, SMPN 2 Palengaan, and SMPN Satu Atap Pengantin Pria. Data sources are the principal, curriculum vice principal, teachers, and students. Data collection through observation, interviews, and document studies. Data analysis techniques are data collection, coding, organizing, verification, conclusions, and triangulation. The results of the study indicate that character education in the Independent Curriculum can be implemented through various subjects and extracurricular activities. Students can integrate Madurese cultural values â€‹â€‹and have mutual symbiosis with the surrounding natural environment so as to foster awareness of the environment and recognize cultural identity. Success is influenced by teacher competence, sufficient resources, parental and community support, termination of doctrine, classroom management, utilization of the surrounding environment as a learning resource, and continuous evaluation. This innovation has an impact on increasing social values, creativity, cultural pride, environmental awareness, and students’ ability to think in solutions to ecological and cultural issues.